Effects of Bacterial Melanin on Neuronal Spike Activity in the Rat Sensorimotor Cortex - Petrosyan, T.R.; Gevorgyan, O.V.; Hovsepyan, A.S.; Ter-Markosyan, A.S. (Нейрофизиология, 2015)
We examined post-stimulation changes in the electrical activity of neurons of the rat sensorimotor cortex after intapraperitoneal injections or direct applications of bacterial melanin (a strict analog of neuromelanin). Activation of cortical neurons was evoked by highfrequency stimulation of the hindlimb peripheral nerves. The patterns of within-stimulation responses and long-lasting post-stimulation effects were rather similar in both subgroups (with systemic introductions or direct applications of melanin). Comparison of the results of previous electrophysiological experiments, where the effects of melanin on electrical activity generated by neurons of the substantia nigra pars compacta were studied, showed close similarities of the effects of this agent (mostly activating influence of bacterial melanin with the predominance of excitatory/facilitatory post-stimulation modifications of spike activity). The effects of bacterial melanin can contribute to the recovery processes in neurodegenerative diseases.